2019
DOI: 10.1159/000499431
|View full text |Cite
|
Sign up to set email alerts
|

Atopic Patients Show Increased Interleukin 4 Plasma Levels but the Degree of Elevation Is Not Sufficient to Upregulate Interleukin-4-Sensitive Genes

Abstract: <b><i>Background:</i></b> Atopic diseases constitute a major health challenge for industrialized countries, and elevated levels of interleukin 4 (IL-4) frequently characterize these disorders. Previous in vitro<i></i>analyses have indicated that IL-4 strongly upregulates the expression of IL-4-sensitive genes in human monocytes. <b><i>Objective:</i></b> To explore whether similar expression alterations may contribute to the pathomechanisms of atopic d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
(62 reference statements)
0
5
0
2
Order By: Relevance
“…genes demonstrated in vitro [9]. As a consequence, biologics that target IL-13 alone may be efficacious for controlling AD.…”
Section: Targeted Biological Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…genes demonstrated in vitro [9]. As a consequence, biologics that target IL-13 alone may be efficacious for controlling AD.…”
Section: Targeted Biological Therapymentioning
confidence: 99%
“…The overexpression of IL‐13 in AD skin contributes to the vicious cycle of inflammation, skin‐barrier dysfunction, and microbiome dysbiosis [5, 6]. In addition, it has been suggested that in vivo IL‐4 levels are not high enough to impact the expression of IL‐4‐sensitive genes demonstrated in vitro [9]. As a consequence, biologics that target IL‐13 alone may be efficacious for controlling AD.…”
Section: Targeted Biological Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Dupilumab, ein Antikörper der an den IL-4-Rezeptor (IL-4Rα) bindet und sowohl IL-4-als auch IL-13-Signale verhindert, ist gegenwärtig für die Behandlung von AD, Asthma und chronischer Rhinosinusitis mit Polyposis zugelassen. In neueren Studien wurde IL-13 als häufigstes Typ-2-Zytokin in läsionaler Haut bei AD identifiziert, wobei das Expressionsniveau von IL-13 in den Hautläsionen mit der Schwere der Erkrankung korreliert [5][6][7][8][9]. Die Überexpression von IL-13 in der AD-Haut trägt zum Teufelskreis von Entzündung, Störung der Hautbarriere und Dysbiose des Mikrobioms bei [5,6].…”
Section: Zielgerichtete Topische Therapieunclassified
“…Die Überexpression von IL-13 in der AD-Haut trägt zum Teufelskreis von Entzündung, Störung der Hautbarriere und Dysbiose des Mikrobioms bei [5,6]. Außerdem wird vermutet, dass die Konzentration von IL-4 in vivo nicht hoch genug ist, um die, in vitro nachgewiesene, Expression IL-4-sensitiver Gene zu beeinflussen [9]. Folglich können Biologika, die gezielt nur gegen IL-13 gerichtet sind, AD möglicherweise wirksam kon-trollieren.…”
Section: Zielgerichtete Topische Therapieunclassified